Cognitive Impairment and Psychopathology Are Related to Plasma Oxidative Stress in Long Term Hospitalized Patients With Chronic Schizophrenia - Yang, Man; Li, Jin; Yang, Haidong; Yan, Linya; Liu, Dongliang; Zhu, Lin; Zhang, Xiaobin (Frontiers in Psychiatry, 2022)
Background: The present study aimed to examine whether plasma oxidative stress is associated with cognitive impairment in long term hospitalized patients with chronic schizophrenia. Method: Ninety-six chronic schizophrenia patients and ninety-four healthy unaffected subjects were enrolled. Plasma markers of oxidative stress, including malondialdehyde (MDA), manganese superoxide dismutase (MnSOD), catalase (CAT), and glutathione peroxidase (GSH-Px), were measured. Psychiatric symptoms and cognitive function were assessed with the Positive and Negative Syndrome Scale (PANSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), respectively. Results: Plasma MDA levels and MnSOD and GSH-Px activities were significantly lower in schizophrenia patients than in healthy controls (P < 0.001), while plasma CAT activity was higher than in healthy controls (P < 0.005). Cognitive scores on the RBANS and all of its five subscales (all P< 0.001) were significantly lower in schizophrenia patients than in healthy unaffected subjects. CAT and GSH-Px activities were positively correlated with the cognitive function scores corresponding to Visuospatial/Constructional abilities in the patient group (r = 0.298, 0.213, respectively, P < 0.05).Also, the multiple regression analysis revealed that CAT and GSH-Px activities were independent and separate contributors to the Visuospatial/Constructional index of the RBANS. Meanwhile, CAT activity was negatively correlated with general pathological symptoms (r = -0.307, Bonferroni corrected P = 0.008) and the total score of the PANSS domains (r = -0.299, Bonferroni corrected P = 0.012). Conclusion: Our results that the reduced of MDA level and the increased CAT activity in plasma in male patients with chronic schizophrenia suggest that redox imbalance may be associated with the pathophysiology of schizophrenia, and it can induce impaired cognition and psychiatric symptoms.